2017
DOI: 10.1155/2017/8639898
|View full text |Cite
|
Sign up to set email alerts
|

Versatility of Chitosan-Based Biomaterials and Their Use as Scaffolds for Tissue Regeneration

Abstract: Chitosan is a naturally occurring polysaccharide obtained from chitin, present in abundance in the exoskeletons of crustaceans and insects. It has aroused great interest as a biomaterial for tissue engineering on account of its biocompatibility and biodegradation and its affinity for biomolecules. A significant number of research groups have investigated the application of chitosan as scaffolds for tissue regeneration. However, there is a wide variability in terms of physicochemical characteristics of chitosan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 91 publications
0
30
0
2
Order By: Relevance
“…As mentioned above the porosity and pore size of the scaffold material is critical for ingrowth of capillaries, therefore based on the decrease in pore size and porosity caused by the modification a reduced vascularization could be anticipated for the CS-g-PCL coated samples. Furthermore chitosan is biocompatible and biodegradable, therefore being well known as a biological material which promotes the healing process of soft and hard tissues [41]. The immobilization of CS-g-PCL on top of electrospun PCL fibers by crystallization resulted in the modification of all fibers also within the material and not only on the surface like other techniques as e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above the porosity and pore size of the scaffold material is critical for ingrowth of capillaries, therefore based on the decrease in pore size and porosity caused by the modification a reduced vascularization could be anticipated for the CS-g-PCL coated samples. Furthermore chitosan is biocompatible and biodegradable, therefore being well known as a biological material which promotes the healing process of soft and hard tissues [41]. The immobilization of CS-g-PCL on top of electrospun PCL fibers by crystallization resulted in the modification of all fibers also within the material and not only on the surface like other techniques as e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan is a natural polymer derived from the alkaline N‐deacetylation of chitin, which is widely used in pharmaceutical and biomedical applications thanks to its useful characteristics of biodegradability, biocompatibility, low toxicity and moldability . Its molecular structure is very close to that of the glycosaminoglycans that compose the ECM, which renders it an ideal candidate as supportive material for the preparation of scaffolds intended for tissue engineering . In particular, the use of chitosan in oral and maxillofacial applications is particularly interesting because of its contribution to wound healing, and its intrinsic antibacterial activity against some common oral pathogens .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Its molecular structure is very close to that of the glycosaminoglycans that compose the ECM, which renders it an ideal candidate as supportive material for the preparation of scaffolds intended for tissue engineering. 9,10 In particular, the use of chitosan in oral and maxillofacial applications is particularly interesting because of its contribution to wound healing, 11,12 and its intrinsic antibacterial activity against some common oral pathogens. 13 In order to improve the ability of chitosan to act as a substrate for cell growth, 14 the preparation of chitosan films in the presence of phosphates and D-(+)-raffinose was described, which positively contributed to the growth of WI-38 and HUVEC cells on this biomaterial.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is a kind of mucopolysaccharide widely existed in nature, which is important component of connective tissue with complexation, bacteriostasis, adsorption, and antioxidant effects (Molinaro et al, 2002;Jayakumar et al, 2005). Recent reports demonstrated that chitosan can be gelated in an acidic pH or a non-solvent condition (Ribeiro et al, 2017;Xu et al, 2017;Chen Y. R. et al, 2019), and further be prepared for chitosanbased hydrogel scaffolds. Chitosan has good biocompatibility and biodegradability; therefore, it is a kind of tissue-engineering material with wide application prospects and can be considered as a potential material for cartilage repair in regenerative medicine fields.…”
Section: Chitosanmentioning
confidence: 99%